Optimization of the Linker Length of Mannose-Cholesterol Conjugates for Enhanced mRNA Delivery to Dendritic Cells by Liposomes - Wang, Fazhan; Xiao, Wen; Elbahnasawy, Mostafa A.; Bao, Xingting; Zheng, Qian; Gong, Linhui; Zhou, Yang; Yang, Shuping; Fang, Aiping; Farag, Mohamed M. S.; Wu, Jinhui; Song, Xiangrong (Frontiers in Pharmacology, 2018)
Liposomes (LPs) as commonly used mRNA delivery systems remain to be rationally designed and optimized to ameliorate the antigen expression of mRNA vaccine in dendritic cells (DCs). In this study, we synthesized mannose-cholesterol conjugates (MPn-CHs) by click reaction using different PEG units (PEG100, PEG1000 and PEG2000) as linker molecules. MPn-CHs were fully characterized and subsequently used to prepare DC-targeting liposomes (MPn-LPs) by a thin-film dispersion method. MPn-LPs loaded with mRNA (MPn-LPX) were finally prepared by a simple self-assembly method. MPn-LPX displayed bigger diameter (about 135 nm) and lower zeta potential (about 40 mV) compared to MPn-LPs. The in vitro transfection experiment on DC2.4 cells demonstrated that the PEG length of mannose derivatives had significant effect on the expression of GFP-encoding mRNA. MP1000-LPX containing MP1000-CH can achieve the highest transfection efficiency (52.09 ± 4.85%), which was significantly superior to the commercial transfection reagent Lipo 3K (11.47 ± 2.31%). The optimal DC-targeting MP1000-LPX showed an average size of 132.93 ± 4.93 nm and zeta potential of 37.93 ± 2.95 mV with nearly spherical shape. Moreover, MP1000-LPX can protect mRNA against degradation in serum with high efficacy. The uptake study indicated that MP1000-LPX enhanced mRNA expression mainly through the over-expressing mannose receptor (CD206) on the surface of DCs. In conclusion, mannose modified liposomes might be a potential DC-targeting delivery system for mRNA vaccine after rational design and deserve further study on the in vivo delivery profile and anti-tumor efficacy.